Enterococcal colonization of the gastro-intestinal tract: role of biofilm and environmental oligosaccharides - Fabretti Francesca (BMC Microbiology, 2006)
Abstract Background Biofilm formation in E. faecalis is presumed to play an important role in a number of enterococcal infections. We have previously identified a genetic locus provisionally named bop that is involved in maltose metabolism and biofilm formation. A transposon insertion into the second gene of the locus (bopB) resulted in loss of biofilm formation, while the non-polar deletion of this gene, together with parts of the flanking genes (bopA and bopC) resulted in increased biofilm formation. A polar effect of the transposon insertion on a transcriptional regulator (bopD) was responsible for the reduced biofilm formation of the transposon mutant. Results The amount of biofilm formed is related to the presence of maltose or glucose in the growth medium. While the wild-type strain was able to produce biofilm in medium containing either glucose or maltose, two mutants of this locus showed opposite effects. When grown in medium containing 1% glucose, the transposon mutant showed reduced biofilm formation (9%), while the deletion mutant produced more biofilm (110%) than the wild-type. When grown in medium containing 1% maltose, the transposon mutant was able to produce more biofilm than the wild-type strain (111%), while the deletion mutant did not produce biofilm (4%). Biofilm formation was not affected by the presence of several other sugar sources. In a gastrointestinal colonization model, the biofilm-negative mutant was delayed in colonization of the mouse intestinal tract. Conclusion The biofilm-positive phenotype of the wild-type strain seems to be associated with colonization of enterococci in the gut and the presence of oligosaccharides in food may influence biofilm formation and therefore colonization of enterococci in the gastrointestinal system.